PENGEMBANGAN BAHAN AJAR INTERAKTIF ERA TEKNOLOGI 5.0 - Octaviany, Fany; Faika, Sri; Hidayat, Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore the development of interactive teaching materials in the Technology 5.0 era, which involves the integration of advanced technologies such as AI, AR and VR in the learning process. Using the literature review method, this research analyzes the characteristics, benefits, challenges and potential of interactive teaching materials in improving the quality of education. The study results show that interactive teaching materials can increase student engagement and motivation, facilitate understanding of complex concepts, and provide a more personalized and adaptive learning experience. While there are challenges related to costs, infrastructure and training requirements, the benefits are far more significant. This research suggests the need for further investment in technological infrastructure, educator training, and research to optimize the application of interactive teaching materials in education.